All Hands on Deck : Reducing Stunting through Multisectoral Efforts in Sub-Saharan Africa - Skoufias, Emmanuel; Vinha, Katja; Sato, Ryoko (Washington, DC: World Bank and Agence française de développement, 2019)
In Sub-Saharan Africa, the scale of undernutrition is staggering; 58 million children under the age of five are too short for their age (stunted), and 14 million weigh too little for their height (wasted). Poor diets in terms of diversity, quality, and quantity, combined with illness and poor water and sanitation facilities, are linked with deficiencies of micronutrients—such as iodine, vitamin A, and iron—associated with growth, development, and immune function.